Fabrication of core-shell nanoparticles for protein delivery - Koh, Weixiang (2016)
The objective of this study is to optimize the formation of Layer-by-layer (LbL) polyelectrolyte nano-capsules, using nano-sized CaCO3 as templates. LbL technique involves the consecutive assembly of oppositely charged electrolytes based on electrostatic interactions onto charged template surfaces. Apart from improving the formation of CaCO 3 nanoparticles, the optimisation of conditions for the formation of hollow capsules, using CaCO3 as template core, was experimented on as well. In many of the current studies, micro-sized CaCO3 template cores are being used in the formation of LbL hollow capsules for drug delivery applications. However, their large sizes have always posed problems when it comes to extending their application into real biological scenarios. Nano-sized capsules are known to have higher efficiency in crossing biological barriers and an increased circulation time when it is introduced into the blood system. These problems might be rectified with the use of nano-sized CaCO3 template cores, for the formation of hollow capsules. Therefore, it is imperative to form and optimize nano-sized CaCO3 particles that can be used as template cores for the formation of hollow capsules. In this study, biopolymers such as protamine and CMC have been used as polyelectrolyte coatings to form these hollow capsules. This is because biopolymers generally show low toxicity and are biodegradable. The relative ease of preparation through the LbL self-assembly, accurate control over the wall thickness as well as the flexibility in the choice of constituents makes LbL carriers a good fit for the delivery of sensitive macromolecular drugs such as functional proteins. Functional protein drugs are extremely sensitive and, usually, large in size which has often resulted in difficulties related to encapsulation processes. Therefore, there is a considerable challenge in the encapsulation of these protein drugs into the nano-sized LbL assembled carriers. The active protein used for the treatment of AMD, Lucentis, was used as a model drug in the loading and release experiments in this study. AMD is a degenerative eye disease which affects the retina. It is one of the leading causes of blindness in today’s industrialized world. Therefore, it is important to ensure that there are improvised treatment methods to tackle the disease. Hence, experiments are carried out in this study to attempt to encapsulate and also to understand the release of these molecules.